Provenance of the Devonian–Carboniferous clastics of the southern part of the Prikolyma terrane (Verkhoyansk–Kolyma orogen) based on U–Pb dating of detrital zircons. (2nd October 2019) - Prokopiev, Andrei V.; Ershova, Victoria B.; Stockli, Daniel F.
ABSTRACT: U–Pb dating of detrital zircons collected from the Middle–Upper Palaeozoic strata of the Prikolyma terrane (Verkhoyansk–Kolyma orogen) provide the first insight into provenance areas and the Middle–Late Palaeozoic geological history of the Russian Far East. Detrital zircon ages from the Lower–Middle Devonian sandstones group around 395–405 M (Emsian–Eifelian) which correlate well to trachyte of the Uvyazka zone and the Kedon Complex of the North Okhotsk active continental margin located on the Omolon terrane. Precambrian-aged zircons group around 1740–2080 and 2460–2800 Ma, respectively, suggesting possible sources within metamorphic rocks of the basement of the Omolon terrane or the Siberian Craton. The majority of the zircons from the Lower and Upper Carboniferous sandstones group around 333–375 Ma, suggesting that the principle source of the clastics were volcanic rocks and comagmatic felsic intrusions of the Kedon Complex of the North Okhotsk active continental margin. Our new data allow us to evaluate and revise the available palaeotectonic reconstructions of northeast Asia for the Devonian and Carboniferous.